Research on the hydration process of solid waste–based cementitious materials and application in roadbase - Chu, Feng; Li, Chuanhai; Wu, Chuanshan; Wang, Yansheng (Frontiers in Energy Research, 2024)
In order to improve the high-value utilization of industrial solid waste materials, this study prepared a solid waste-based cementitious material (SWCM) using slag, fly ash, desulfurization gypsum and gangue. The mechanical strength and hydration process of SWCM and an ordinary Portland cement (OPC) were studied. The results showed that the compressive strength of SWCM were lower than those of OPC at 3d, but the compressive strength exceeded those of OPC after 7d. The isothermal calorimetry results showed that the induction period of the SWCM was 5 times of that of OPC, and the total 4d exothermic amount of OPC was 1.7 times that of SWCM. The XRD and SEM showed that the hydration products of the SWCM were mainly ettringite (AFt) and hydrated calcium silicate gel (C-S-H). The unconfined compressive strength and dry shrinkage of stabilized macadam were also studied by using SWCM to replace OPC. The results indicated that the unconfined compressive strength of the SWCM stabilized macadam is comparable to that of the OPC stabilized macadam. The dry shrinkage strain was only 79.7 % of OPC stabilized macadam.